Plyometric anatomy : your illustrated guide to explosive power - Hansen, Derek, ....-; Kennelly, Steve, ....- (Champaign : Human Kinetics, 2017)
Elite players, coaches, and trainers rely on plyometrics to develop power, agility, speed, strength, body control, balance, and overall athletic performance. With this authoritative guide on plyometrics, you can too! In Plyometric Anatomy, authors Derek Hansen, coach and consultant to elite athletes and professional and collegiate sports teams, and Steve Kennelly, assistant head athletic trainer for the New York Football Giants, share the training they've used to propel athletes at all levels to success. They present 94 plyometric exercises, with 78 variations that increase in difficulty for continued development over time. Each exercise is fully illustrated with detailed anatomical art to showcase the muscles that are activated during the drill, so you can clearly see how the exercise contributes to improved performance. You'll also find unique plyometric exercises and variations that combine upper- and lower-body muscles in a single drill to better simulate complex sport-specific movements. Plus, considerations such as the impact of performing the drills on various surfaces, commonly used equipment, and use of external loads are included to make sure you get the most from your training. With comprehensive coverage and expert insights, Plyometric Anatomy takes the guesswork out of training and provides the best tool to help you achieve dynamic strength and explosive power. It is the ultimate illustrative resource for maximizing athletic power production.
Keywords: Krachttraining